Curriculum and evaluation in the frame of the 1290 government decree of 2009: policies or pedagogies? - Díaz Ballén, José Emilio (Universidad Pedagógica y Tecnológica de Colombia, 2010)
Evaluation has been a weak excuse and a practice raised to a decisive category, when there is a pretension to revise what occurs inside education. The evaluation act is added to all those that are structured and conveyed into the functioning of the different school centers. The leading role assigned to the evaluation and the deployment of an ideological infrastructure allows empowering it with two particular aims: To measure the “quality” of the different process that are carried out in the school institutions, and to measure the periodical results, trying to make them a public referent stand. The student’s learning process is being reformulated according the educational policies and to the normative conditions. In the case of the 1290 decree of 2009, the students learning evaluation is equalized to some minimal achievements standards in the frame of the development of some market demanded competences, which have little to provide to the integral formation for the children and youngsters that are educated in the Colombian Educational System.